Phytochemical study of Tribulus Terrestris L. - A. Affaf; Yu. N. Karpenko; D. K. Gulyaev; V. D. Belonogova; E. I. Molokhova; O. L. Blinova; A. A. Gileva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2020)
Tríbulus terrestris L., an annual herb belonging to the Zygophyllaceae family and growing in moderate and tropical climates, has a rich chemical composition of biologically active substances and chemical elements.The aim of the work is a phytochemical study of Tribulus terrestris L. growing in different geographical zones.Materials and methods. The objects of study were herb specimens of Tribulus terrestris L. collected in different habitats. The samples of the raw materials were shade-dried. The determination of saponins in the raw materials, was carried out by high performance liquid chromatography with a mass spectrometric detection (HPLC-MS / MS). The study of the qualitative and quantitative composition of the elements was carried out on an X-ray fluorescence spectrometer.Results. The saponins had been studied by HPLC-MS/MS, according to which in all the studied samples, dioscin and protodioscin were found. Their retention times coincided with the retention times of dioscin and protodioscin standards. It has been established that among the macroelements of Tríbulus terrestris L., potassium and calcium are mostly accumulated. They account for about 90% of the total content of the elements in the plant. It has been revealed that the distribution of macroand microelements in the plant, varies significantly depending on their place and growing conditions.Conclusion. The maximum dioscin content was observed in the samples harvested in Moldova, and the minimum - in the samples from the nursery garden of the All-Russian Scientific Research Institute of medicinal and aromatic plants. The largest amount of protodioscin was found out in the samples from the Crimea, and the minimum - in the samples from Moldova. The carried out study of the elements content of Tríbulus terrestris L. showed that the habitats (geographical zones) in which the studied samples of raw materials had been were collected, affect the accumulation of the elements by the plant. Based on the data obtained, biological absorption series have been compiled for the samples from each habitat.